Synthesis of 20‐Membered Macrocyclic Pseudo‐Natural Products Yields Inducers of LC3 Lipidation. Issue 11 (25th January 2022) - Niggemeyer, Georg; Knyazeva, Anastasia; Gasper, Raphael; Corkery, Dale; Bodenbinder, Pia; Holstein, Julian J.; Sievers, Sonja; Wu, Yao‐Wen; Waldmann, Herbert
Abstract: Design and synthesis of pseudo‐natural products (PNPs) through recombination of natural product (NP) fragments in unprecedented arrangements enables the discovery of novel biologically relevant chemical matter. With a view to wider coverage of NP‐inspired chemical and biological space, we describe the combination of this principle with macrocycle formation. PNP‐macrocycles were synthesized efficiently in a stereoselective one‐pot procedure including the 1, 3‐dipolar cycloadditions of different dipolarophiles with dimeric cinchona alkaloid‐derived azomethine ylides formed in situ. The 20‐membered bis‐cycloadducts embody 18 stereocenters and an additional fragment‐sized NP‐structure. After further functionalization, a collection of 163 macrocyclic PNPs was obtained. Biological investigation revealed potent inducers of the lipidation of the microtubule associated protein 1 light chain 3 (LC3) protein, which plays a prominent role in various autophagy‐related processes. Abstract : The combination of three natural product fragments in 20‐membered macrocyclic pseudo‐natural products led to the discovery of inducers of a novel LC3 lipidation phenotype.